PERAN SUVENIR DALAM MENINGKATKAN CITRA DESTINASI WISATA - Edy Semara Putra (Jurnal Pariwisata PaRAMA : Panorama, Recreation, Accomodation, Merchandise, Accessbility, 2026)
This study explores the role of souvenirs in enhancing the image of tourist destinations. As tangible representations of a location's cultural identity, souvenirs function not only as keepsakes but also as indirect marketing tools that promote the destination. Using a qualitative descriptive method, this research reviews the literature on the positive impacts of souvenirs on tourist experiences and perceptions. The findings reveal that tourists value unique and authentic products, which foster emotional connections to destinations. Moreover, the shopping experience significantly influences tourist satisfaction and loyalty. Well-crafted souvenirs contribute to a destination's economic sustainability and strengthen its competitive position in the global tourism market.